(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
Several Schiff bases derived from salicyaldehyde have been synthesized and characterized. The Schiff bases derivatives of saliylidene has been studied by means of elemental analysis, Ms, IR, 1H and 13C NMR spectra. The spectra are discussed and compared with of compounds N.N-1.2-cyclohexylene bis(salicylideneimine), N.N’-1.2-cyclohexylene bis(5-bromo salicylideneimine) and ,4.4’- diaminodiphenylsulfon bis(salicylideneimine). Strong intramolecular forces are present as supported by the IR and 1H NMR spectra. Separation of Cu2+ and Cr3+ from aqueous solution using 4.4’-diaminodiphenylsulfon bis(salicylideneamine) as new solvent for extraction has been studied. The Schiff base has been studied by liquid–liquid extraction towards the metal ions (UO22+)and d-metal ions (Hg2+, Co2+ and Cr3+) from aqueous phase to organic phase. جرى اصطناع ودراسة عدة مركبات من أسس شيف مشتقة من ساليسيل ألدهيد وشخصت بالتحليل العنصري ومطيافية ما تحت الأحمر والرنين النووي المغناطيسي الهيدروجيني والكربوني. نوقشت وقورنت المطيافية بين مركبات N’.N-2.1-حلقي هكسيل بيس (ساليسيليدين ثنائي الايمين) وN’.N-2.1- حلقي هكسيل ثنائي (5-برمو ساليسيليدين ثنائي الايمين) و 4’.4- ثنائي امين ثنائي فينيل سلفون ثنائي (ساليسيليدين ثنائي الايمين). أكدت النتائج المسجلة لطيوف IR و NMR للمركبات المدروسة وجود روابط قوية بين الجزئيات. درس فصل شوارد معدني الكروم والنحاس من المحاليل المائية باستخدام مركب 4’.4-ثنائي امينو ثنائي فينيل سلفون بيس ( ساليسيليدين ثنائي الامين) بوصفه من المركبات الواعدة للاستعمال مستقلاً في استخلاصها والتخلص منها. درس أساس شيف السابق باستخلاص ايونات المعادن الانتقالية بعمليات سائل-سائل تجاه ايونات UO22+ والمعادن الانتقالية مثل Hg2+, و Co2+ و Cr3+ لإخراجها من الطور المائي إلى الطور العضوي.